MAKNA SIMBOL PROPERTI PADA SAJIAN TARI PINGAN SUKU DAYAK MUALANG DESA MENAWAI TEKAM - Agustina, Paula; Istiandini, Winda; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is motivated to know about the meaning of the symbol of property on the dish dance Pingan Dayak tribe Mualang Village Menawai Tekam Sekadau District. The method used is descriptive method with qualitative form and using approach of ethnokoreologi, with source data of John Roberto Panurian, Lusi, Gansi who know about the symbol of property at dish Pingan dance. Data obtained from observation, interview, and documentation. Pingan dance is a dance that created as legitimation (validation) of a person for his ability to complete martial arts / martial arts learned to fight against the enemy. The first property is Pingan which symbolizes the offering of public gratitude to Petara (God) has the meaning as an inspiration medium to build the relationship between man and God. Pingan is not only used as a mere aesthetic tool but rather the fulfillment of the pleasures of the human senses and soul. The second property of Tincin which became the symbol of sound has the meaning as the delivery of human soul to Petara (God). This has the meaning that sound represents human language which is not conveyed directly through words or utterances